The effect of body weight-supported overground gait training for patients with Parkinson's disease: A retrospective case-control observational study. - Yasuki Koyanagi; Isato Fukushi; Masatoshi Nakamura; Kouji Suzuki; Nobuhito Oda; Takashi Aita; Hareaki Seki (PLoS ONE, 2021)
Objective To evaluate the effects of body weight-supported overground gait training (BWSOGT) on motor abilities, such as gait and balance, in patients with Parkinson's disease (PD). Design Retrospective case-controlled observational study with a 4-week follow-up. Setting Inpatient rehabilitation. Participants We selected 37 of 68 patients with PD. Inclusion criteria were (1) Hoehn & Yahr stage II-IV, (2) no medication adjustment during the study period, (3) at least 1 week since last medication adjustment, and (4) ability to walk more than 10 meters on their own. Exclusion criteria were (1) cerebrovascular disease or other complications affecting movement, (2) difficulty in measurement, (3) early discharge, (4) medication change during the study, and (5) development of complications. Interventions Patients were divided into two groups. Patients in Group I underwent 20 minutes of BWSOGT with a mobile hoist in addition to the standard exercises; Group II performed 20 minutes of gait training in place of BWSOGT. In both groups, training was performed for a total of 15 times/4 weeks. Main outcome measure(s) Participants were evaluated using the Unified Parkinson's Disease Rating Scale total, part II, and part III; 10-m walk test; velocity; stride length; 6-minute walk test; timed up and go test; Berg Balance Scale; and freezing of gait before and after the intervention. Results There were significant decreases in the Unified Parkinson's Disease Rating Scale total, part II, and part III in both groups; however, 6-minute walk test, timed up and go test, and freezing of gait results only improved in Group I. Conclusions BWSOGT for patients with PD improves gait ability and dynamic balance more than standard gait training.